Removal of the N-terminal hexapeptide from human beta2-microglobulin facilitates protein aggregation and fibril formation. - Esposito, G; Michelutti, R; Verdone, G; Viglino, P; Hernández, H; Robinson, C; Amoresano, A; Dal Piaz, F; Monti, M; Pucci, P; Mangione, P; Stoppini, M; et al. (2000)
The solution structure and stability of N-terminally truncated beta2-microglobulin (deltaN6beta2-m), the major modification in ex vivo fibrils, have been investigated by a variety of biophysical techniques. The results show that deltaN6beta2-m has a free energy of stabilization that is reduced by 2.5 kcal/mol compared to the intact protein. Hydrogen exchange of a mixture of the truncated and full-length proteins at microM concentrations at pH 6.5 monitored by electrospray mass spectrometry reveals that deltaN6beta2-m is significantly less protected than its wild-type counterpart. Analysis of deltaN6beta2-m by NMR shows that this loss of protection occurs in beta strands I, III, and part of II. At mM concentration gel filtration analysis shows that deltaN6beta2-m forms a series of oligomers, including trimers and tetramers, and NMR analysis indicates that strand V is involved in intermolecular interactions that stabilize this association. The truncated species of beta2-microglobulin was found to have a higher tendency to self-associate than the intact molecule, and unlike wild-type protein, is able to form amyloid fibrils at physiological pH. Limited proteolysis experiments and analysis by mass spectrometry support the conformational modifications identified by NMR and suggest that deltaN6beta2-m could be a key intermediate of a proteolytic pathway of beta2-microglobulin. Overall, the data suggest that removal of the six residues from the N-terminus of beta2-microglobulin has a major effect on the stability of the overall fold. Part of the tertiary structure is preserved substantially by the disulfide bridge between Cys25 and Cys80, but the pairing between beta-strands far removed from this constrain is greatly perturbed.